Mothers' and Fathers' Perspectives on the Causes of Their Child's Disorder. (17th July 2020) - Felnhofer, Anna; Bussek, Theresa; Goreis, Andreas; Kafka, Johanna X; König, Dorothea; Klier, Claudia; Zesch, Heidi; Kothgassner, Oswald D
Abstract: Background: Parental beliefs about the cause of their child's illness are thought to affect parents' help-seeking behaviors, treatment decisions, and the child's health outcomes. Yet, research on parental beliefs about disease causation is still scarce. While a small number of studies assesses parental cause attributions for singular disorders (e.g., neurodevelopmental disorders), no study has compared disorders with differing physical versus mental conditions or with mixed comorbidities in children and adolescents or their caregivers. Furthermore, most pediatric research suffers from a lack of data on fathers. Objective: Hence, the objective of the current study was to test for possible differences in mothers' and fathers' perceptions about the etiology of their child's illness. Methods: Forty-two parent couples (overall N = 84) whose child had been diagnosed either with Attention Deficit Hyperactivity-Disorder (ADHD) or Autism Spectrum Disorder (ASD) (category "neurodevelopmental disorder") or with a primary physical illness and a comorbid mental disorder, e.g. depression (category "psychosomatic disorder") were asked to rate possible causes of their child's illness using a modified version of the revised Illness Perception Questionnaire (IPQ) Cause scale. Results: A two-way ANOVA showed that psychosomatic disorders were significantly more strongly attributed to be caused by medical and environmental stressors than neurodevelopmental disorders. A significant parent × illness category interaction revealed that this effect was more pronounced in fathers. Conclusions: By providing first insights into parental beliefs about the etiology of their children's neurodevelopmental versus psychosomatic disorders, this study paves ground for future research and tailored counseling of affected families.